2020
DOI: 10.1111/jvim.15746
|View full text |Cite
|
Sign up to set email alerts
|

Renin‐angiotensin aldosterone profile before and after angiotensin‐converting enzyme‐inhibitor administration in dogs with angiotensin‐converting enzyme gene polymorphism

Abstract: Background An angiotensin‐converting enzyme (ACE) gene polymorphism occurs in dogs; however, functional importance is not well studied. Hypothesis We hypothesized that dogs with the polymorphism would show alternative renin‐angiotensin aldosterone system (RAAS) pathway activation and classical RAAS pathway suppression before and after ACE‐inhibitor administration, as compared to dogs without the polymorphism that would show this pattern only after ACE‐inhibitor administration. Animals Twenty‐one dogs with mitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
44
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(49 citation statements)
references
References 25 publications
(103 reference statements)
4
44
1
Order By: Relevance
“…These results increase our understanding of drug effects on the traditional APs, driven by ACE, while simultaneously offering insight into the counterbalancing alternative arm, driven by ACE2. Our study, along with others, 19,22,26 demonstrates that ACEI treatment in dogs with heart disease is associated with relatively low production of APs that are primarily dependent on ACE, particularly AT2, which is produced by cleavage of 2 amino acids from AT1. Our data expand our understanding of ACE production of Ang1‐7, which occurs by ACE‐mediated cleavage of 2 amino acids from Ang1‐9, and also of Ang1‐5, which is produced by cleavage of 2 amino acids from Ang1‐7.…”
Section: Discussionsupporting
confidence: 72%
“…These results increase our understanding of drug effects on the traditional APs, driven by ACE, while simultaneously offering insight into the counterbalancing alternative arm, driven by ACE2. Our study, along with others, 19,22,26 demonstrates that ACEI treatment in dogs with heart disease is associated with relatively low production of APs that are primarily dependent on ACE, particularly AT2, which is produced by cleavage of 2 amino acids from AT1. Our data expand our understanding of ACE production of Ang1‐7, which occurs by ACE‐mediated cleavage of 2 amino acids from Ang1‐9, and also of Ang1‐5, which is produced by cleavage of 2 amino acids from Ang1‐7.…”
Section: Discussionsupporting
confidence: 72%
“…The influence of breed on RAAS activity could be related to differences in genes encoding for RAAS components. Polymorphism of angiotensin-converting enzyme gene has been found in several breeds, including CKCS and Chihuahua, but it has been suggested that it could be more common in certain breeds [47][48][49]. Little is known about the effect of this polymorphism on RAAS components in dogs, but, as previously reported in humans [50], a recent study has found higher aldosterone levels and ABT incidence in MMVD dogs with ACE polymorphism after enalapril treatment and in presence of adequate ACE-A-II suppression, suggesting that this genotype could be involved in the upregulation of alternative pathways for aldosterone secretion [47].…”
Section: Discussionmentioning
confidence: 99%
“…Polymorphism of angiotensin-converting enzyme gene has been found in several breeds, including CKCS and Chihuahua, but it has been suggested that it could be more common in certain breeds [47][48][49]. Little is known about the effect of this polymorphism on RAAS components in dogs, but, as previously reported in humans [50], a recent study has found higher aldosterone levels and ABT incidence in MMVD dogs with ACE polymorphism after enalapril treatment and in presence of adequate ACE-A-II suppression, suggesting that this genotype could be involved in the upregulation of alternative pathways for aldosterone secretion [47]. Furthermore, polymorphism of genes encoding for angiotensinogen, A-II type 1 receptor, aldosterone synthase and chymase have been reported in humans and may also be present in dogs [51][52][53][54].…”
Section: Discussionmentioning
confidence: 99%
“…Inhibitors of ACE are used clinically to reduce the formation of angiotensin II, thereby mitigating these effects which contribute to cardiovascular and renal disease progression, fluid retention, and systemic hypertension [1,2]. Clinically effective RAAS suppression by ACE-inhibitors, however, is sometimes sub-optimal because of aldosterone breakthrough, non-ACE mediated angiotensin II formation, genetic variants affecting RAAS components, feedback mechanisms, and likely other unidentified factors [3][4][5][6][7]. The ACE gene intronic variant at canine chromosome 9:11507816:G > A has recently been shown to increase the magnitude of aldosterone breakthrough, despite adequate suppression of angiotensin II by ACEinhibitors [4].…”
Section: Introductionmentioning
confidence: 99%
“…Clinically effective RAAS suppression by ACE-inhibitors, however, is sometimes sub-optimal because of aldosterone breakthrough, non-ACE mediated angiotensin II formation, genetic variants affecting RAAS components, feedback mechanisms, and likely other unidentified factors [3][4][5][6][7]. The ACE gene intronic variant at canine chromosome 9:11507816:G > A has recently been shown to increase the magnitude of aldosterone breakthrough, despite adequate suppression of angiotensin II by ACEinhibitors [4]. Genotype influence on non-angiotensin mediated aldosterone production holds clinical implications for dogs with advanced heart disease in both disease expression and response to treatments, but the prevalence of this variant in the canine population is unknown.…”
Section: Introductionmentioning
confidence: 99%